2019
DOI: 10.21138/bage.2830
|View full text |Cite
|
Sign up to set email alerts
|

Overtourism in urban destinations: the myth of smart solutions

Abstract: The rapid increase in urban tourism flows generates problems of tourist overcrowding and gives rise to important challenges for city management. Within this context, urban tourism planning is experiencing a convergence of new paradigms related to the so-called Smart Tourist Destinations (SD). Smart tourism and its operational level open up new avenues for intervention in the city which can help to manage overtourism. Therefore, the objective of this study is to analyse the level of implementation of sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 28 publications
(21 reference statements)
0
20
0
Order By: Relevance
“…It also highlights the important role of local governments in the planning process, as they are most familiar with local communities' interests and problems [32,33]. By analyzing the implementation level of smart solutions, Hernández et al (2019) showed that Spanish local governments had developed no technological solutions to address overtourism issues in the four destinations of Donostia-San Sebastián, Madrid, Málaga, and Valencia [34]. Furthermore, it has been stated that a difference exists between the perception of residents and management organizations about overtourism [35].…”
Section: Literature Review 21 Historic Cities and Challenges Of Overtourismmentioning
confidence: 99%
“…It also highlights the important role of local governments in the planning process, as they are most familiar with local communities' interests and problems [32,33]. By analyzing the implementation level of smart solutions, Hernández et al (2019) showed that Spanish local governments had developed no technological solutions to address overtourism issues in the four destinations of Donostia-San Sebastián, Madrid, Málaga, and Valencia [34]. Furthermore, it has been stated that a difference exists between the perception of residents and management organizations about overtourism [35].…”
Section: Literature Review 21 Historic Cities and Challenges Of Overtourismmentioning
confidence: 99%
“…Carrying capacity is the precursor to current concerns with overtourism, and it is not a new concept [60]. Overtourism is a complex, multicausal phenomenon that is transforming tourism and tourism policies in urban environments [2]. Lopez Palomeque [61] has already pointed out that, in Barcelona, this phenomenon would justify moving from sectoral promotion policies towards a structural and transversal approach.…”
Section: Overtourismmentioning
confidence: 99%
“…Lopez Palomeque [61] has already pointed out that, in Barcelona, this phenomenon would justify moving from sectoral promotion policies towards a structural and transversal approach. Garcia Hernandez et al [2] summarised the pressure indicators, the impacts and the response measures and found that when there is a significant impact of overload, the tourist experience is affected (negatively) and this is reflected in social media reviews [62], such as TripAdvisor. A possible measure to deal with overtourism is to apply smart solutions [2] or reposition the destination as a place of special tourism interest by focusing on a particular type of experience [63].…”
Section: Overtourismmentioning
confidence: 99%
See 1 more Smart Citation
“…Smart tourism promises a unique opportunity for renewal after crises, such as the COVID-19 pandemic, as well as a tangible approach to rethinking the way technology is conceptualized and implemented so that it can serve emerging tourism agendas (Gretzel et al, 2020). It also provides a concrete pathway towards sustainability (Ivars-Baidal, Vera-Rebollo, Perles-Ribes, Perles-Ribes & Ivars-Baidal, 2018), including the avoidance of overtourism (García Hernández, Baidal, & Mendoza de Miguel, 2019), and offers guidelines for ethical and just destination governance (Gretzel & Jamal, 2020). In addition, it promises a way to render a destination more resilient by facilitating communication flows and resource mobilization, thus making it possible to better prepare for, address, or even avoid a crisis (Gretzel & Scarpino-Johns, 2018).…”
Section: Introductionmentioning
confidence: 99%